Nutritional Status of Pregnant Mothers Influence the Health in Adult Life of their Children - Echarte, E.M.; Rocío, Abalo; Chisari, A.N. (Journal of Nutritional Therapeutics, 2015)
Pregnancy and fetal development are periods of rapid growth and cell differentiation when mother and offspring are vulnerable to changes. Adverse events during development can be linked to an increased risk in developing metabolic diseases. Growth restriction in utero is associated with the development of obesity, hypertension, and diabetes. In these processes, the liver plays a fundamental role. The aim of this work was to evaluate the effects of a low protein diet in pregnant and lactating mothers on the antioxidant status of the offspring liver. To reproduce real conditions, we used an experimental rat model. Both ROS and the protective antioxidant systems have to work in coordination to reach a state of redox homeostasis. Excess generation of ROS may result in cell death or different pathological processes. The study also highlights the complex nature of malnutrition injury in which ROS correlates with the hepatic injury in a cause-and-effect manner. The male offspring with intrauterine growth restriction (IUGR) caused by the isocaloric low-protein diet (8%) showed decreased liver and body weight at birth. Hepatic cholesterol levels and serum transaminase increase, at weaning (24 day of age). We observed excess generation of ROS, carbonyl group and lipoperoxidation with that may result in cell death or different pathological processes in the liver. Conclusion: This study would suggests that liver injury due to accelerated release of toxic oxygen species and impaired antioxidant status may contribute to the high susceptibility to suffer metabolic diseases, that are related to diet in early life and that manifest in adulthood.